The effectiveness of science encyclopedia-assisted project-based learning integrated with the STEM approach in enhancing pre-service elementary teachers’ scientific literacy - Badaruddin, Amiruddin; Budi, Agus Setyo; Sumantri, Mohamad Syarif (Journal of Education and e-Learning Research, 2024)
Scientific literacy plays a crucial role for elementary teachers in developing the strategies of science learning and implementing them in the classroom. Nevertheless, the scientific literacy of college students in elementary education has not been optimal. Science encyclopedia-assisted project-based learning (PjBL) integrated into the science, technology, engineering and mathematics (STEM) approach is hypothesized to enhance scientific literacy. The present study describes and examines the effectiveness of science encyclopedia-assisted STEM-PjBL in enhancing pre-service elementary teachers’ scientific literacy. Quasi-experimental research using a pre- and post-tests control group design was applied to this study. 56 pre-service elementary teachers at the University of Halu Oleo were involved in this study whereby they were equally distributed to two groups. A test of scientific literacy was adapted and used to measure scientific literacy. Descriptive and inferential statistics were used to describe and analyse the data of scientific literacy. Results revealed that science encyclopedia-assisted STEM-PjBL had a positive modest effect on the achievement of scientific literacy. The scientific literacy of college students in elementary education who received science encyclopedia-assisted STEM-PjBL had moderate enhancement. Additionally, a science encyclopedia-assisted STEM-PjBL significantly enhanced scientific literacy. Educational practitioners can implement a science encyclopedia-assisted PjBL integrated STEM approach to enhance scientific literacy resulting in high achievement in science education.